WAYS TO IMPROVE THE FINANCIAL EFFICIENCY OF THE USE OF INVESTMENTS IN THE SECTORS OF THE NATIONAL ECONOMY - Namozov Olim Botirovich (American Journals, 2024)
This article provides for the development, discussion and conclusions based on the study of the specifics of the theoretical foundations of the development of sources and methods of financing investment projects in national economy.
Keywords: Investment, investor, investment activity, financing, investment projects, sources of financing, stock markets, real investments, financial investments.